COVID-19 and cross-border contagion: Trade and financial flows - Achraf Louati; Zakaria Firano; Fatine Filali Adib (Research in Globalization, 2022)
In this article, we examine the effects of the COVID-19 pandemic on the dynamics of contagion in the economic and financial spheres. The objective of the article is to confirm that the systemic nature of contagion risk is greater in extreme situations than in normal situations. Through this study we want to highlight the nature of contagion and the transmission of shocks in both the economic and financial spheres. Similarly, we have tried to measure the dynamics of contagion processes in normal situations and also those of crises. This work contributes to the current and recent debate on the risk of cross-border contagion and in particular in a health crisis. Using graph theory, information theory and Markov chains, we were able to verify that the systemic risk of contagion was significantly increased during the lockdown and that the commercial and financial dynamics changed during this period (between March 2020 and June 2020). Similarly, our results state that the extreme degree of contagion risk is predictable via Markov chains by pre-emptively using medium-voltage cycles that are precursors of systemic crises.
Keywords: F36; F65; B17; 330; Contagion; Systematic risk; COVID-19; Markov chain; Trade; Graph theory; Financial markets